EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAY DALAM MENINGKATKAN PERILAKU KEDISIPLINAN PADA ANAK DIDIK SD (KELAS 3) - Faiza Ni’mah Fillah; Meilla Dwi Nurmala; Bangun Yoga Wibowo (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to determine the effectiveness of group guidance with role play techniques in improving disciplinary behavior. quantitative approach with quasi-experimental method in the form of quasi-experimental design through nonequivalent control group Group consisting of 78 populations with 22 research samples. This study uses Purposive Sampling technique. And using primary data in the form of questionnaires and providing treatment in the form of pretest and post-test with role play as the results of the study so that it shows that there is an influence between the role play variable (X) on disciplinary behavior (Y) on aspects of discipline, which consists of discipline Mental attitude (mental attitude), discipline in enforcing rules, discipline attitude and discipline in behavior.